2012
DOI: 10.1002/sca.21001
|View full text |Cite
|
Sign up to set email alerts
|

AFM Study for Morphological Characteristics and Biomechanical Properties of Human Cataract Anterior Lens Capsules

Abstract: The aim of this study was to quantitatively investigate the morphologies (surface roughness) and biomechanical properties (Young's modulus) of human anterior lens capsules (ALCs) for noncataract and cataract groups using atomic force microscopy. Eight human ALCs obtained during phacoemulsification from patients with senile cataracts (72 ± 13 years) were investigated in both the hydrated and dehydrated conditions. The cataract group showed clearly the proliferated lens epithelial cells (LECs) with a monomorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Capsular tears in FS laser assisted cataract surgery have been mainly reported to occur with hydrodissection and during lens manipulations [ 12 ], suggesting that reduced capsular distensibility may represent an additional factor to increased risk of capsular tears during FS laser assisted cataract surgery. On the other hand, there is still no evidence supporting this hypothesis [ 17 19 , 23 25 , 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capsular tears in FS laser assisted cataract surgery have been mainly reported to occur with hydrodissection and during lens manipulations [ 12 ], suggesting that reduced capsular distensibility may represent an additional factor to increased risk of capsular tears during FS laser assisted cataract surgery. On the other hand, there is still no evidence supporting this hypothesis [ 17 19 , 23 25 , 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Oliver‐Pharr method the contact stiffness can be calculated from the unloading part of the load‐indentation curve (Oliver and Pharr, ). It has been reported that the initial data of the unloading curve is almost linear for some materials, and as a result a linear fit is the most obvious solution regarding the upper portion of the curve (Fischer‐Cripps, ; Choi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, AFM is gaining popularity in ophthalmology and has been used to image other basement membranes in the eye. 1,8,9,13,24,25,46 The images obtained in the current study are similar to those acquired of other basement membranes in the eye: a dense interwoven fibrous structure separated by openings on the order of a micron.…”
Section: Discussionmentioning
confidence: 76%